Fenomena Sosial dalam Novel Ancika Karya Pidi Baiq - Yolanda, Feza Herli; Elyusra2 , Elyusra (EduInovasi: Journal of Basic Educational Studies, 2024)
This problem is: Social phenomena, various social phenomena and various norms, factors of social phenomena, the impact of social phenomena in the novel Ancika by Pidi Baiq?. The aim of this research is: To describe social phenomena, various social phenomena, factors of social phenomena, the impact of social phenomena in the novel Ancika by Pidi Baiq. The method in this research is a descriptive analysis method. The results of the research state as follows: 1) Social phenomena in the novel Ancika by Pidi Baiq. Based on data analysis, social phenomena were found in the novel Ancika by Pidi Baiq. From the results of reading the novel, 90 data were collected containing social phenomena. Data analysis states that there are 9 social phenomena described by the author. 2) Various social phenomena in the novel Ancika by Pidi Baiq. Based on data analysis, various kinds of social phenomena were found in the novel Ancika by Pidi Baiq. There were 6 types found, namely: 1) Habitual norms, 2) Moral norms, 3) Legal norms, 4) Narcotics abuse, 5) Corruption, 6) Religious norms. 3) Factors of social phenomena in the novel Ancika by Pidi Baiq. Based on data analysis, various kinds of social phenomena were found in the novel Ancika by Pidi Baiq. There were 2 types of factors found, namely: 1) Structural factors, 2) Cultural factors. 4) The impact of social phenomena in the novel Ancika by Pidi Baiq. Based on data analysis, various kinds of social phenomena were found in the novel Ancika by Pidi Baiq. There were 2 types of impacts found on social phenomena, namely: 1) Positive impacts, 2) Negative impacts. The suggestions are as follows: 1) For readers, the author hopes that this research will increase readers' appreciation of literary works. 2) For literary researchers, this research can be the beginning of inspiration for researchers themselves to be able to make better research, especially in researching literary works.  3) For future researchers, future researchers should be able to conduct research more perfectly, both related to this research, and related to other problems in research with the object of the novel Ancika by Pidi Baiq.